Density functional study of structural, electronic and magnetic properties of new half-metallic ferromagnetic double perovskite Sr2MnVO6. (21st August 2019) - Rahmani, Neda; Ghazi, M E; Izadifard, Morteza; Wang, Duo; Shabani, Alireza; Sanyal, Biplab
Abstract: In this paper, a new half-metallic (HM) double perovskite compound is predicted with the simultaneous presence of ferromagnetism and polar distortion. The structural, electronic and magnetic properties of Sr2 MnVO6 (SMVO) are calculated by density functional theory (DFT) with both generalized gradient approximation (GGA) and GGA + U approaches, where U is the on-site Coulomb interaction parameter. Different orderings of B (B′) cationic sites in A2 BB′O6 double perovskite structure are evaluated, including rocksalt, columnar and layered arrangements for cubic, monoclinic and tetragonal crystal structures. It is found that the most stable ordering is obtained when B and B′ are placed in a layered type ordering for a tetragonal crystal structure with I4/m space group, which is confirmed by phonon calculations. The B-site ordering of the Mn 3+ and V 5+ ions in a layered configuration leads to ferromagnetically coupled magnetic moments of 4.17 µ B at Mn site and 0.23 µ B at V site. Finally, SMVO is found to be a half-metallic ferromagnetic (HM-FM) compound with a band gap of 0.65 eV in a spin down channel with off-centered displacement of V atoms in the octahedral cage (second order Jahn -Teller effect) which can cause ferroelectricity. Therefore, SMVO is predicted to be a polar HM material and a promising candidate for multiferroic property with potential application in spintronics.